Activity of the central bank in the conditions of disturbances on financial markets - Noga, Marian (Publishing House of the Wrocław University of Economics, 2009)
The mission of central banks is managing inflation expectations of all parti-cipants in the market. The strategy of performing that mission is autonomously specified by the central bank of each country or common currency area. The per-formance instruments are also selected in a variety of ways. Thus, the development of a common strategy of pursuing monetary policy by the central bank may be easily criticised. Nevertheless, there were such attempts, especially after 1990. A discussion on the activity of central banks, referred to in the literature as “rules versus discretions”, began at that time. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 345-352